The role of stress echocardiography in transcatheter aortic valve implantation and transcatheter edge-to-edge repair era: A systematic review - Pavasini, Rita; Fabbri, Gioele; Bianchi, Nicola; Deserio, Maria Angela; Sanguettoli, Federico; Zanarelli, Luca; Tonet, Elisabetta; Passarini, Giulia; Serenelli, Matteo; Campo, Gianluca (Frontiers in Cardiovascular Medicine, 2022)
Objectives: In the last decade, percutaneous treatment of valve disease has changed the approach towards the treatment of aortic stenosis (AS) and mitral regurgitation (MR). The clinical usefulness of stress echocardiography (SE) in the candidates for transcatheter aortic valve implantation (TAVI) and transcatheter edge-to-edge repair (TEER) of MR remains to be established. Therefore, the key aim of this review is to assess the main applications of SE in patients undergoing TAVI or TEER. Methods: We searched for relevant studies to be included in the systematic review on PubMed (Medline), Cochrane library, Google Scholar, and Biomed Central databases. The literature search was conducted in February 2022. The inclusion criteria of the studies were: observational and clinical trials or meta-analysis involving patients with AS or MR evaluated with SE (excluding those in which SE was used only for screening of pseudo-severe stenosis) and treated with percutaneous procedures. Results: Thirteen studies published between 2013 and 2021 were included in the review: five regarding candidates for TEER and eight for TAVI. In TEER candidates, seeing an increase in MR grade, and stroke volume of >40% during SE performed before treatment was respectively related to clinical benefits (p=0.008) and an increased quality of life. Moreover, overall, 25% of patients with moderate secondary MR at rest before TEER had the worsening of MR during SE. At the same time, in SE performed after TEER, an increase in mean transvalvular diastolic gradient and in systolic pulmonary pressure is expected, but without sign and symptoms of heart failure. Regarding TAVI, several studies showed that contractile reserve (CR) is not predictive of post-TAVI ejection fraction recovery and mortality in low-flow low-gradient AS either at 30 days or at long-term. Conclusions: This systematic review shows in TEER candidates, SE has proved useful in the optimization of patient selection and treatment response, while its role in TAVI candidates is less defined. Therefore, larger trials are needed to test and confirm the utility of SE in candidates for percutaneous procedures of valve diseases.